A new cytotoxic naphthoquinone from Paepalanthus latipes - Kitagawa, R. R.; Raddi, MSG; dos Santos, L. C.; Vilegas, Wagner [UNESP] (Pharmaceutical Soc Japan, 2004)
Quinones constitute an important class of naturally occurring compounds. They are found in plants, fungi and bacteria. Large number of quinones has been associated with antitumor, antibacterial, antimalarial and antifungal activities. In this work we describe the isolation, structure determination and the cytotoxic index of a new 1,4-naphthoquinone isolated from the capitula of Paepalanthus latipes.
Keywords: naphthoquinone; Paepalanthus; cytotoxicity